2018
DOI: 10.1128/iai.00642-17
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Porcine Alveolar Macrophages by Actinobacillus pleuropneumoniae Lipopolysaccharide via the Toll-Like Receptor 4/NF-κB-Mediated Pathway

Abstract: is the causative agent of porcine contagious pleuropneumonia. Overproduction of proinflammatory cytokines, like interleukin-1β (IL-1β), IL-6, tumor necrosis factor alpha, and resistin, in the lung is an important feature of infection. These proinflammatory cytokines enhance inflammatory and immunological responses. However, the mechanism that leads to cytokine production remains unclear. As a major virulence factor of, lipopolysaccharide (LPS) may act as a potent stimulator of Toll-like receptor 4 (TLR4), trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Bacterial death induces endotoxin release into circulation, often resulting in endotoxemia. In this stage of bacterial infection, pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6 are elevated (Choi et al, 1999 ; Cho and Chae, 2002 ), playing a crucial role in the pathogenesis of acute bacterial infection (Li et al, 2018 ). In this study, secretion of pro-inflammatory cytokines TNF-α, IL-1β, and IL-6 from macrophages were significantly (P < 0.01) promoted after stimulation with GALT (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial death induces endotoxin release into circulation, often resulting in endotoxemia. In this stage of bacterial infection, pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6 are elevated (Choi et al, 1999 ; Cho and Chae, 2002 ), playing a crucial role in the pathogenesis of acute bacterial infection (Li et al, 2018 ). In this study, secretion of pro-inflammatory cytokines TNF-α, IL-1β, and IL-6 from macrophages were significantly (P < 0.01) promoted after stimulation with GALT (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that proinflammatory mediators such as LPS, tumor necrosis factor-alpha (TNF-a), interleukin 1b (IL-1b), and IL-6 can strongly induce the expression of resistin in monocytes/macrophages (12,(46)(47)(48). For instance, Actinobacillus pleuropneumoniae-LPS induces porcine alveolar macrophages to produce resistin via MyD88, TRAM, and NF-kB by interacting with TLR4 (49). Besides, the mRNA expression of resistin is also significantly upregulated in human peripheral blood-derived monocytes following exposure to microfilariae or antigen of Brugia malayi (50,51).…”
Section: Resistin Expression Pattern and Regulationmentioning
confidence: 99%
“…Once infection occurs, AMs move between alveoli to sense and phagocytose inhaled bacteria before they can induce harmful lung inflammation (Neupane et al, 2020 ). Meanwhile, the Gram-negative bacterial LPS binding to the TLR4 of AMs initiates multiple intracellular signaling pathways and induces the production of some pro-inflammatory cytokines, such as interleukin 1β (IL-1β) (Li et al, 2017 ). These pro-inflammatory cytokines induce superfluous neutrophil recruitment, leading to continuous lung inflammation and injury.…”
Section: Introductionmentioning
confidence: 99%